MicroRNAs and long non-coding RNAs in cartilage homeostasis and osteoarthritis - Gu, Jingliang; Rao, Wu; Huo, Shaochuan; Fan, Tianyou; Qiu, Minlei; Zhu, Haixia; Chen, Deta; Sheng, Xiaoping (Frontiers in Cell and Developmental Biology, 2022)
During the last decade, osteoarthritis (OA) has become one of the most prevalent musculoskeletal diseases worldwide. OA is characterized by progressive loss of articular cartilage, abnormal remodeling of subchondral bone, hyperplasia of synovial cells, and growth of osteophytes, which lead to chronic pain and disability. The pathological mechanisms underlying OA initiation and progression are still poorly understood. Non-coding RNAs (ncRNAs) constitute a large portion of the transcriptome that do not encode proteins but function in numerous biological processes. Cumulating evidence has revealed a strong association between the changes in expression levels of ncRNA and the disease progression of OA. Moreover, loss- & gain-of-function studies utilizing transgenic animal models have demonstrated that ncRNAs exert vital functions in regulating cartilage homeostasis, degeneration, and regeneration, and changes in ncRNA expression can promote or decelerate the progression of OA through distinct molecular mechanisms. Recent studies highlighted the potential of ncRNAs to serve as diagnostic biomarkers, prognostic indicators, and therapeutic targets for OA. MiRNAs and lncRNAs are two major classes of ncRNAs that have been the most widely studied in cartilage tissues. In this review, we focused on miRNAs and lncRNAs and provided a comprehensive understanding of their functional roles as well as molecular mechanisms in cartilage homeostasis and OA pathogenesis.